PERANCANGAN PROTOTYPE ALAT PENGHITUNG KELAPA OTOMATIS BERBASIS ARDUINO - RAZALI, AHMAD; Suharyanto, Cosmas Eko (LPPM Universitas Putera Batam, 2020)
Basically, humans are very dependent on the environment around them in everyday life in the form of natural resources that can support human life. Indonesia is one country that is rich in natural resources that provides many benefits such as coconuts and counting coconuts using only makeshift equipment manually, books and pens or counting coconuts using a hand tally counter, thus causing a lack of efficiency in working time. Current technological developments, there have been many technologies designed to help human work directly indirectly both in the office, company/industry, and home. In industrial field, equipment is used manually and can even be replaced by using technological equipment so that it can function automatically, device for counting the number of coconuts through the sensor is a device that can be used in designing a new system that is applied to farmers. technology uses Photodiode and Infrared sensors that function to detect an object. The way the coconut counter works automatically will count the coconut that passes in front of the sensor, Infrared sensor E18-D80NK and displays an output in LCD 16X2 which is the number of coconuts detected by sensor. prototype automatic coconut counter is used when unloading and loading coconuts.